LXR deficiency confers increased protection against visceral Leishmania infection in mice. - Kevin W Bruhn; Chaitra Marathe; Ana Cláudia Maretti-Mira; Hong Nguyen; Jacquelyn Haskell; Thu Anh Tran; Veena Vanchinathan; Upasna Gaur; Mary E Wilson; Peter Tontonoz; Noah Craft (Public Library of Science (PLoS), 2010)
The liver X receptors (LXRs) are a family of nuclear receptor transcription factors that are activated by oxysterols and have defined roles in both lipid metabolism and cholesterol regulation. LXRs also affect antimicrobial responses and have anti-inflammatory effects in macrophages. As mice lacking LXRs are more susceptible to infection by intracellular bacteria Listeria monocytogenes and Mycobacterium tuberculosis, we hypothesized that LXR might also influence macrophage responses to the intracellular protozoan parasite Leishmania chagasi/infantum, a causative agent of visceral leishmaniasis.Surprisingly, both LXRα knock-out and LXRα/LXRβ double-knock-out (DKO) mice were markedly resistant to systemic L. chagasi/infantum infection compared to wild-type mice. Parasite loads in the livers and spleens of these animals were significantly lower than in wild-type mice 28 days after challenge. Bone marrow-derived macrophages from LXR-DKO mice infected with L. chagasi/infantum in vitro in the presence of IFN-γ were able to kill parasites more efficiently than wild-type macrophages. This enhanced killing by LXR-deficient macrophages correlated with higher levels of nitric oxide produced, as well as increased gene expression of IL-1β. Additionally, LXR ligands abrogated nitric oxide production in wild-type macrophages in response to infection.These observations suggest that LXR-deficient mice and macrophages mount antimicrobial responses to Leishmania infection that are distinct from those mounted by wild-type mice and macrophages. Furthermore, comparison of these findings to other intracellular infection models suggests that LXR signaling pathways modulate host antimicrobial responses in a complex and pathogen-specific manner. The LXR pathway thus represents a potential therapeutic target for modulating immunity against Leishmania or other intracellular parasites.